Estudio comparativo del sistema informático AS-400 del IESS con el REDACCA en los procesos de agendacion de citas y control de fichas médicas. - Gastesi Junco, Ronald Adilson (2019)
Nowadays technology has had very significant advances that have encouraged the automation and control of processes in the field of medicine allowing more efficient control of diagnoses and the clinical history of people, reducing the technological gap between medicine and technology. in medical centers in rural areas. In the rural medical clinics of the IESS (Ecuadorian Institute of Social Security), in certain occasions the doctors use the two systems that are: The REDACCA system and the AS-400 system, so there is no correct use of a software that regulates all the information of the patients, causing that the controls and the diagnoses to a certain date are uncertain and confusions in the treatment of the people can arise. According to the representatives of the organization, people do complain because when they come to the medical appointment they realize that there is no record of the previous consultation, it should be mentioned that the consultations or scheduling also do it manually and also the separation of appointments they do from one day to another, in case of an emergency the doctors on duty do not perform a scheduling of said patient. The purpose of this study is to perform an analysis of the two systems proposed and thus determine which would be the best to continue using for the control and scheduling of appointments in the medical clinics of the SSC, safeguarding the safety of patients.